Laryngeal Synovial Sarcoma: A Rare Clinical Entity - Clair Saxby; Ron Bova; Melanie Edwards (Case Reports in Otolaryngology)
Introduction. Synovial sarcomas (SS) are aggressive malignant soft tissue tumours that are thought to arise from pluripotent mesenchymal cells. Clinical Report. A 20-year-old male presented with an acute onset of respiratory stridor. Computer tomography scanning confirmed a mass arising from the left supraglottic larynx and an emergency tracheostomy was performed. A diagnosis of biphasic synovial sarcoma was formed. A total laryngectomy and left hemithyroidectomy was performed in conjunction with a left modified radical neck dissection. The patient received adjuvant chemotherapy followed by a course of radiotherapy and remains alive and disease free at 18 months after treatment. Discussion. Prognosis for patients with SS is related to primary tumour extent, grade, and size. The presence of the diagnostic translocation, t(X;18), is being targeted and hopefully will lead to the development of new therapeutics (Guadagnolo et al., 2007). Conclusion. Laryngeal SS remains a rare and poorly understood entity. A multidisciplinary approach to treatment is essential and long-term followup is imperative.